Outer Ring Iodothyronine Deiodinases and Thyroid Hormone Economy: Responses to Iodine Deficiency in the Rat Fetus and Neonate - Marı́a Jesús Obregón; Carmen Ruiz de Oña; ROSA CALVO; Francisco Escobar del Rey; Gabriella Morreale de Escobar (1991)
Female rats were fed a low iodine diet (LID) or the same diet supplemented with KI (IOD) and mated. Plasma TSH, T4 and T3 in thyroid, plasma, and tissues, and 5'-deiodinase activities (5'D) were measured in maternal, fetal, and neonatal samples. Plasma T4 was markedly reduced in LID dams, TSH was increased, and T3 was normal. Placental T4 was decreased to 10%, and placental T3 to 50%. In LID fetuses there was a complete depletion of both extrathyroidal and intrathyroidal stores of T4 and T3. The thyroid responded with increased synthesis and secretion of T3 over T4, as assessed from the T3 to T4 ratios. Near birth, brain T4 and T3 concentrations were only 6.7% and 12% of those in IOD fetuses, despite a marked increase in brain 5'D-II and a T4-sparing decrease in liver and lung 5'DI. Brown adipose tissue 5'D-II increased 7-fold, and brown adipose tissue T4 and T3 concentrations were only decreased by 50%. After birth, the availability of iodine improved somewhat through maternal milk, and the thyroidal and extrathyroidal pools of T4 and T3 increased, although they remained much lower than those in IOD pups. Brain 5'D-II markedly increased in LID pups, and this together with an increase in plasma and brain T4 ensured almost normal brain T3 during the suckling period. The thyroidal secretion of T3 over T4 continued to be increased in LID pups during the suckling period and appeared to be related to their high circulating TSH levels. Both LID fetuses and newborns can respond to iodine deficiency as adults rats, but the fetus is more sensitive to LID because of its dependence on maternal T4. The success of the adaptative mechanisms in protecting the brain from severe T3 deficiency depends on the supply of iodine, the limiting factor for the synthesis of T4. (Endocrinology129: 2663–2673, 1991)